Impact of different controlled temperature and humidity conditions on the behaviour, posture and spatial needs in fattening rabbits - Contreras-Jodar, Alexandra; Dalmau, Antoni; Bagaria, Marc; Rendon, Marilys; Salama, Ahmed A. K.; Velarde, Antonio (Frontiers in Veterinary Science, 2025)
This study aimed to evaluate the effect of thermal conditions on the posture and behaviour of fattening rabbits and to determine the minimum space allowance and height required in a transport container to allow for thermoregulatory behaviours. Thirty-six rabbits (2.27 ± 0.13 kg) of hybrid genetics were fasted for 6 h and then exposed to three thermal treatments (T1: 15.3°C and 63.0% RH; T2: 22.9°C and 38.3% RH; T3: 31.1°C and 35.5% RH) for 8 h in a climate-controlled chamber. Postural and behavioural responses were continuously recorded via video and subsequently analysed using standardised ethograms. These responses were also analyzed by comparing the first and last 4 h of exposure to assess temporal changes in response to thermal treatments but no significant differences were found between them. The space occupied by each rabbit was quantified through digital image analysis. Results showed that the warmer the thermal treatment, the more frequently the rabbits adopted sprawled postures, while self-grooming and exploratory behaviours decreased and inactivity increased significantly. Rabbits tend to avoid physical contact under higher temperatures, likely as a mechanism to enhance heat dissipation. The space occupied varied with posture: 168 cm2/kg when lying, 205 cm2/kg in sternal sprawl, and 277 cm2/kg in lateral sprawl, corresponding to a stocking density of 60, 49, and 36 kg/m2, respectively. Height needed to perform the different behaviours ranged from 13 cm in sprawled positions to 32 cm when upright. During the 8 h treatment, rabbits spent approximately 1% of the time in upright posture, suggesting limited use of vertical space. In T1, rabbits require a minimum of 168 cm2/kg (60 kg/m2) to lie down all at the same time. In T2 and T3, rabbits require 205–277 cm2/kg (36–49 kg/m2) to allow sprawling in static, non-ventilated conditions. A cage height of ≥ 35 cm is necessary for rabbits of this weight to stand upright. These findings highlight the importance of adjusting space allowance and height in transport containers based on thermal conditions to safeguard rabbit welfare during transport. These experimental results need validation under commercial transport conditions.